2018
DOI: 10.1186/s12998-018-0196-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the old to the new: A comparison of similarities and differences of the accreditation standards of the chiropractic council on education-international from 2010 to 2016

Abstract: BackgroundChiropractic programs are accredited and monitored by regional Councils on Chiropractic Education (CCE). The CCE-International has historically been a federation of regional CCEs charged with harmonising world standards to produce quality chiropractic educational programs. The standards for accreditation periodically undergo revision. We conducted a comparison of the CCE-International 2016 Accreditation Standards with the previous version, looking for similarities and differences, expecting to see so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Papers in this series have again revealed deeply rooted disagreements within the chiropractic profession about what chiropractic is, and what it should be, as a profession [13,19,20], as well as disagreements and variation in relation to education of chiropractors [14,15] and chiropractic clinical practice [11]. In our opinion, it is ironic that while chiropractic has a strong presence in large parts of the world [3], is taking on increasingly important roles in disability prevention [6,7,17], in the military [5] and in interprofessional care [8] as well as growing research capacity [16], discussions about fundamental values and direction of the profession are unresolved.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Papers in this series have again revealed deeply rooted disagreements within the chiropractic profession about what chiropractic is, and what it should be, as a profession [13,19,20], as well as disagreements and variation in relation to education of chiropractors [14,15] and chiropractic clinical practice [11]. In our opinion, it is ironic that while chiropractic has a strong presence in large parts of the world [3], is taking on increasingly important roles in disability prevention [6,7,17], in the military [5] and in interprofessional care [8] as well as growing research capacity [16], discussions about fundamental values and direction of the profession are unresolved.…”
Section: Discussionmentioning
confidence: 98%
“…Two papers reported on issues relating to education of chiropractors. Innes et al compared accreditation standards from the Councils of Chiropractic Education between 2010 and 2016 and found that while there had been a move towards a focus on musculoskeletal care, mention of competencies in appraising scientific evidence and evidence-based practice had been removed from the criteria [14]. Funk et al searched websites of 46 chiropractic educational programs in order to identify and count the mention of the term subluxation, and found that it is much more prevalent in descriptions of US-based educational institutions, and in fact the mention of subluxation had increased between 2011 and 2017 [15].…”
Section: Commentarymentioning
confidence: 99%
“…Not surprisingly, the views of CCE experts were that accreditation standards were a result of compromises made to reconcile diverse and strongly held opinions about the scope of chiropractic practice in order to accommodate all practitioners' perspectives [25]. This view is reinforced by the knowledge that subsequent revisions of standards have shown few signs of addressing undesirable consequential graduate practices and an unwillingness to adopt key standards accepted by other mainstream allied health care providers [29,30]. This has included, among other strategies, a lack of clear definitions for key terms such as "chiropractor", "diagnosis", and "competency", a lack of a whole-hearted acceptance of an evidence-based approach to standard educational development and clinical practice [29], and silence on known historically important traditional beliefs that have consequences for unwanted practitioner behaviours (subluxation / vitalism) [27,31].…”
Section: Examining the Insights Of Those Within Ccesmentioning
confidence: 99%
“…These include matters involving CP staff, chiropractic registration and licensing boards, chiropractic associations, government departments, health consumer groups, and the public at large. Until recently there has been a paucity of research exploring chiropractic education standards, however recent studies have begun to critically review those making the standards (CCEs) [24,25], chiropractic students who are engaged in the learning (as dictated by the standards) [23,26,27] and the standards themselves [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…While revisions of the CCE-International accreditation standards for chiropractic programs have been reviewed for changes over time [22] no study has explored expectations for graduating chiropractors. Consequently, we chose to investigate the graduate competencies of one CCE, namely the CCE-A for such changes.…”
Section: Problemmentioning
confidence: 99%